Inadequacy of cervical cancer screening among urban recent immigrants: A population-based study of physician and laboratory claims in Toronto, Canada - Lofters, Aisha; Glazier, Richard H.; Agha, Mohammad M.; Creatore, Maria I.; Moineddin, Rahim (Preventive medicine, 2007)
In Canada, Pap smears are recommended from 18 to 69. Self-reported socioeconomic gradients in screening have been documented in North America but there have been few direct measures of Pap smear use among immigrants or socially disadvantaged groups. Our purpose was to investigate whether socioedemographic factors are related to cervical cancer screening in Toronto, Canada. Pap smears were identified using fee and laboratory codes in Ontario physician service claims for 3 years (2000–2002 inclusive) for women aged 18–66. Area-level socioeconomic factors were derived from the 2001 census. At the individual level, recent registrants for health coverage, over 80% of whom are expected to be recent immigrants, were identified as women first registering after January 1, 1993. Among 724,584 women, 55.4% had Pap smears within 3 years. Recent immigration, visible minority, foreign language, low income and low education were all associated with significantly lower area rates. Recent registrants had much lower rates than non-recent registrants (36.9% versus 60.9%). Pap smear rates in Toronto fall below those dictated by evidence-based practice. Recent registrants, a largely immigrant group, have particularly low rates. Efforts to improve coverage need to emphasize women who recently immigrated and those with socioeconomic disadvantage.